Sintagmatiese leksikale betrekkinge in Afrikaans - de Stadler, L.G. (Lexikos, 1991)
Syntagmatic Lexical Relations in Afrikaans Since the work by Porzig (1934) it has come to be accepted that syntagmatic lexical relations (a type of lexical relation that holds between two lexical items on a syntagmatic level, such as the relationship between dog and bark) has to be incorporated in a theory of lexical structure. Although quite a number of scholars have dealt with the phenomenon over the years, one has to agree that it suffers from a long tradition of neglect. As far as linguistic research in Afrikaans goes, no substantial work has been done. In this article I will contrast syntagmatic relations with its paradigmatic counterparts, draw attention to different types of syntagmatic relations and show what relevance this phenomenon has for lexicography.